New Technologies for Project-Based Empathy Learning in Merdeka Belajar (Freedom to Learn): The Use of inaRISK Application and Biopore Technology - Isroatul Khusna, Nur; Sumarmi; Bachri, Syamsul; Astina, I Komang; Wahyu Nurhayati, Dwi Astuti; P Shresthai, Rajendra (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The Freedom to Learn curriculum in higher education provides autonomous and flexible learning that is innovative, independent, and relevant to student needs. The use of new technologies such as inaRISK and biopore in project-based consideration learning is thought to be able to improve students’ cognitive, affective, and psychomotor abilities. The purpose of this study was to determine the effect of using the inaRISK application and biopori technology in project based empathy learning. This research used a mixed method with a research and development (R n D) methods to determine the effectiveness of the learning model, a quasi-experiment to measure cognitive aspects, and applied descriptive statistics to measure affective and psychomotor aspects. To analyze R n D using ADDIE method then cognitive aspects, this research used homogeneity test, normality test, and t-test using SPSS 21 for Windows. The overall analysis (cognitive, affective, and psychomotor aspects) made use of a data sub code system through MAXQDA software, while network analysis was done by using Gephi 0.9.2 software. The results showed that there was a significant and positive influence of the inaRISK application and biopore technology on the students’ cognitive, affective, and psychomotor aspects in the project-based consideration learning of Freedom to Learn.